Герои Великой Отечественной: рассказы ; для детей младшего и среднего школьного возраста / Алексеев Сергей Петрович ; худ. В. В. Юдин - Алексеев Сергей Петрович (Наше Отечество, 2010)
Экземпляры: ф.1 (2010) / Инвентарный номер: 46339 / Цена: / Авт.знак: А 47 / ББК: 63.3(2)622.8